Allelism of ser (JBM5) and ser-3 on linkage group I - J. B. Maxwell; J. Anesi; S. Cadwe; V. Coffman; R. Hoefke; R. Nolan; T. Parker; D. Toon (Fungal Genetics Reports, 1978)
Allelism of ser (JBM5) and ser-3 on linkage group I